Crime, Justice and Social Democracy
XXVII, 365 p.
Keywords: This is a provocative collection of timely reflections on the state of social democracy and its inextricable links to crime and justice. Authored by some of the world's leading thinkers from the UK, US, Canada and Australia, the volume provides an understanding of socially sustainable societies.